NEUROMYELITIS OPTICA SPECTRUM DISORDER (NMOSD) DENGAN ANTIBODI AQP4 POSITIF - Rima Febry Lesmana; Anak Agung Mas Putrawati Triningrat; Made Paramita Wijayanti; I Made Agus Kusumadjaja; Ida Ayu Sri Indrayani; Gede Kambayana (The Indonesia Neurological Association Branch of Denpasar, 2021)
Background: Neuromyelitis optica (NMO) is an in?ammatory demyelinating autoimmune disease of the central nervous system that most commonly affects the optic nerves and spinal cord. Seropositive antiAQP4 differentiates NMO from MS and the presence of manifestation in the postrema, brainsteam or diencephalic areas extend to NMO Spectrum Disorder (NMOSD). Case Description: A 18 years old male complain sudden vision loss on his left eye since 2 weeks ago. The examination show the visual acuity on the right eye was 6/6 and LPBP on the left eye. Positive RAPD on the left eye, funduscopy and the OCT RNFL within normal limits. Head MRI focus orbita with contrast show optic neuritis. Patient was diagnosed with left eye retrobulbar optic neuritis and ONTT therapy was given. The visual acuity improved to 1/60 then therapy change to oral steroid. Four months later, the patient suddenly got vision loss on the right eye accompanied by paraparesis. The visual acuity on the right eye was NLP and the left eye was 1/300, with mid-dilated papil. The results of the OCT RNFL show on the right eye edema papil and left eye atrophy papil. An MRI of the head focus orbital and whole spain was reexamined followed by VEP examination and an AntiAQP4 which showed an NMOSD. He was given ONTT then continued with immunosuppressants. The visual acuity of the right eye improved to 3/60 and the left eye remained 1/300. Discussion: This patient first presented with complain on the left eye with clinical and supporting symptoms suggesting an optic neuritis. The presence of a new attack on the right eye with paraparesis is a clinical feature of NMO supported by MRI results and seropositive AQP4 indicates an NMOSD. Conclusion: Establishment of diagnosis and administration of therapy quickly and precisely can reduce the severity and risk of recurrence which leads to greater disability and blindness. Key Words: Neuromyelitis Optica, Neuromyelitis Optica Spectrum Disorder, AQP4